THE ECONOMIC DEVELOPMENT OF THE REGIONS AS A FACTOR OF STRATEGIC FOCUS - Sofya Aykazovna Tsaturyan (Современная наука и инновации)
The article describes the development of the region from the point of view of economic trends. Attention is drawn to the programme for the development of economic stability in the region, which includes the problems and solutions to situations.